Fatal rupture of pulmonary artery pseudoaneurysm after thoracic radiation therapy against lung squamous cell carcinoma: A case report and literature review - Yosuke Fukuda; Tetsuya Homma; Tomoki Uno; Yasunori Murata; Shintaro Suzuki; Eisuke Shiozawa; Masafumi Takimoto; Hironori Sagara (Clinical Case Reports, 2021)
Abstract Pulmonary artery pseudoaneurysm is a rare but fatal condition. It has been associated with lung cancer, abscesses, and radiation therapy. Identification in patients with hemoptysis is critical, and timely interventional therapy is warranted.